2006
DOI: 10.1080/02770900500498477
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Cough Variant Asthma: A Retrospective Analysis

Abstract: Patients with cough variant asthma, a common cause of chronic cough, may develop wheezing. We examined the determinants of this phenomenon and achievement of remission in 42 patients. During 4 years after diagnosis, wheezing developed in 13 of the patients. Early inhaled corticosteroid treatment was inhibitory against the development of wheezing by univariate analysis and by multivariate analysis with an odds ratio of 0.12 (95% confidence interval, 0.02 to 0.87, p = 0.037). Remission was achieved in 7 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…In fact, the decreased MMP9 to TIMP1 ratio in the bronchial secretion of asthmatic patients has been clearly shown to be associated with chronic airflow obstruction (Bossé et al, 1999;Matsumoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the decreased MMP9 to TIMP1 ratio in the bronchial secretion of asthmatic patients has been clearly shown to be associated with chronic airflow obstruction (Bossé et al, 1999;Matsumoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies show that early application of ICS therapy reduces the risk of progression of CVA to classical asthma [8,12,21]. Namely, an average of 30% of patients with CVA without treatment develop classic asthma with wheezing in the future [3,7].…”
Section: Therapymentioning
confidence: 83%
“…Improvement of chronic cough with bronchodilators is the essential diagnostic feature of CVA [12,13,21].…”
Section: Biomarkers and Diagnostic Criteriamentioning
confidence: 99%
“…In contrast, atopic cough was thought to progress to classic asthma less frequently, especially with early introduction of treatment with ICSs [Fujimura et al 2003]. Similarly, Matsumo and colleagues revealed that treatment with ICSs prevent progression from cough-variant asthma to classic asthma [Matsumoto et al 2006]. Fujimura and colleagues examined the effects of ICSs on changes in AHR and cough reflex sensitivity in patients with cough-variant asthma [Fujimura et al 2005a[Fujimura et al , 2005b.…”
Section: Treatment Of Atypical Asthmamentioning
confidence: 99%